2019
DOI: 10.3390/en12224268
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Sand Production during Depressurization Exploitation in Hydrate Silty-Clay Sediments

Abstract: Silty-clay reservoirs are a weak point in sand production and sand control studies due to their low economy. However, China’s marine natural gas hydrates (NGH) mostly exist in silty-clay sediments, which restrict the sustainable and efficient development of NGH. In order to study the sand production of hydrate silty-clay sediments, hydrate production experiments in vertical wells and horizontal wells were carried out using a self-developed hydrate sand production and sand control simulation device. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…In the first field production test of the Mallik project in 2007, the production period was only 1.5 days due to the occurrence of sand production [10]. Sand production can lead to production well clogging, and excessive stress concentrated around the production well can cause the well to collapse [43]. Therefore, in future studies, productivity and stability analyses that consider the effects of sand production are required.…”
Section: Limitations and Further Workmentioning
confidence: 99%
“…In the first field production test of the Mallik project in 2007, the production period was only 1.5 days due to the occurrence of sand production [10]. Sand production can lead to production well clogging, and excessive stress concentrated around the production well can cause the well to collapse [43]. Therefore, in future studies, productivity and stability analyses that consider the effects of sand production are required.…”
Section: Limitations and Further Workmentioning
confidence: 99%
“…The temperature in this figure refers to the temperature of the reservoir after the formation of hydrates. Data shown are from refs , , , , , , , , , , , and .…”
Section: Gas Production By Depressurization-based Methodsmentioning
confidence: 99%
“…After hydrate dissociation (for about 32 min for sandy GHBSs; 110 and 90 min for clayey-silty GHBSs when saturation was 20% and 30%, respectively), the temperature increased very slowly due to the exchange of heat with the surroundings. 20,29,31 For all samples, the outlet pressure decreased from 10 to 0.1 MPa within 40 min. However, owing to the different characteristics of samples, the inlet pressure showed different depressurization characteristics.…”
Section: Temperature-pressure Responses During Depressurizationmentioning
confidence: 96%
“…12 The subsidences in the vertical and horizontal wells of clayey-silty GHBSs would easily lead to mudflow and large-scale sand production, and a mud cake would form around the wellbore with the water production rate decreasing. 20 The tests on samples from the Liwan area of the Northern South China Sea also reported that very fine silt GHBS was prone to sand production. 21 The experimental work mentioned above focused either on sandy or clayey-silty GHBS separately, which are unable to be compared directly due to the different conditions of the experiments.…”
Section: Introductionmentioning
confidence: 96%